Technology innovation in construction, the time is now - Ghio, Virgilio; Bascuñán W, Roberto (Revista Ingeniería de Construcción, 2006)
This article discusses the main aspects of technology innovation in construction and particularly the needs and possibilities currently present in Chile. The authors conclude that the introduction of cutting edge technologies in construction is especially convenient today in Chile due to several converging circumstances: (a) sustained economy growth, (b) advance in communication technologies that facilitate technology transfer, (c) improved competitivenes of construction industry in the local and international context, (d) and good research in the national level. The article discusses the factors that make a successful technology transfer and the impact of such innovations with the other parts of the project. Finally, the article presents the different alternatives for financing innovative technologies for construction companies.